Fuzzy inference model for decision support in sustainable production planning processes—a case study - Zarte, Maximilian (2021)
Due to crises (e.g., climate crisis, extinction of species, shortage of natural resources, human health crisis), customer requirements for conventionally produced products shift to more sustainably produced products, reducing and avoiding negative environmental and social impacts. Circular thinking in production systems offers new opportunities to meet these new customer expectations. However, it enlarges new challenges for production planning too. Research gaps exist in production planning approaches, considering all three sustainability aspects (economic, environ-mental, and social) simultaneously. This paper presents a concept of a fuzzy inference model (FIM) to assess the sustainability of production programs. The FIM concept is demonstrated and tested using a single case study considering lab production schedules. The model’s outcome indicates the most significant opportunities to improve production programs’ sustainability using experts’ knowledge.